The role of MSMEs (Micro, Small and Medium Enterprises) in improving the national economy - Mahfud, Imam (Privietlab, 2025)
In the era of globalization, development relies heavily on the economic sector as a benchmark for governmental success. Society's contribution to national development, particularly in the economic realm, is embodied by Micro, Small, and Medium Enterprises (MSMEs). MSMEs occupy a crucial and strategic position within the national economy. ​MSMEs have continued to grow year after year since the economic crisis. This also proves that MSMEs can survive amidst economic turmoil. Thus, MSMEs are considered to play a strategic role in reducing unemployment and poverty. Given the contributions and roles of MSMEs, the government must continue supporting MSMEs through reinforcement so that their role as pillars in building the nation’s economy can function optimally. This study aims to understand the contribution of MSMEs to the economy. In addition, this study identifies the challenges and obstacles faced by MSMEs in the national economy. Library research was used, utilizing articles published in international and national journals related to the role of MSMEs in improving the national economy. The results of this study show that MSMEs contribute significantly to the national economy, although their implementation faces challenges. However, the government is striving to provide a range of stimuli to address these issues, so that MSMEs can continue to grow and become empowered.